Analisis Dampak Positif Visual Branding terhadap UMKM: Studi Kasus Pada Brodo dan Adorable Projects - Elisabet Valentina Sianturi; Eka Noviana (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
This research analyzes the positive impact of visual branding on the development and market position of MSMEs through case studies on Brodo and Adorable Projects. Visual branding is a crucial element in shaping consumer perceptions and increasing the competitiveness of MSMEs amidst increasingly fierce industrial competition. This research uses semiotic analysis methods to examine the visual signs in the logo, colors, typography and other elements that are the visual characteristics of the two brands. The analysis was carried out using a semiotic qualitative approach. Effective visual branding not only strengthens brand identity in the market, but also creates a positive emotional connection with consumers. This study confirms the importance of investing in attractive, consistent and culturally relevant visual elements to build sustainable and highly competitive MSME brands.